A Narrative Approach to Understanding the Development of Cultural Intelligence Among Migrant Domestic Workers (Journal of Advanced Research in Social Sciences, 2021)
Filipino migrants all over the world naturally engage in encounters that necessitate the use of cultural intelligence (CQ) or the ability to interact effectively with people who are culturally different. Studies have shown that CQ improves the well-being of workers and aids in their adjustment in foreign environments. This study examines CQ development among migrant domestic workers who worked in Middle Eastern, East Asian, and Southeast Asian countries. A narrative approach was utilized to make sense of the data gathered from the semi-structured interviews with twelve migrant Filipina domestic workers. Findings show that trainings prior to migration, self-initiated strategies for cultural learning, environmental factors, pagtitiis or perseverance during migration, and adopting cultural values from their former host countries are crucial in the development of their CQ. This study highlights the need for further research on the development of CQ in the informal migrant sector. Our findings contribute to the dearth of qualitative research on CQ and its development, and these may be useful for manpower agencies and governments with migrant workers.